2019
DOI: 10.1080/15427560.2018.1492579
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Disposition Effect

Abstract: We investigate the disposition effect building on Realization Utility Theory and Big Five Model. Our experimental analysis, combining NEO IP-R personality measures with individual financial data from a trading simulation run by 230 individuals, shows that the disposition effect is driven by two distinct psychological processes, one related to holding losers and the other to selling winners. These two behavioral mechanisms are uncorrelated and influenced by different personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 80 publications
6
28
2
Order By: Relevance
“…The factor analysis, performed as part of the item analysis, enabled us to extract, from the scale dedicated to the disposition effect, two independent variables (very weak Spearman's rank correlation r = 0.040, and not significant p-value = 0.782), namely cutting gains and holding losses. This finding is in line with previous works (Cecchini et al, 2019;Grayson, 2017;Frydman et al, 2014). Indeed, these authors also found that cutting gains and holding losses are two uncorrelated biases.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The factor analysis, performed as part of the item analysis, enabled us to extract, from the scale dedicated to the disposition effect, two independent variables (very weak Spearman's rank correlation r = 0.040, and not significant p-value = 0.782), namely cutting gains and holding losses. This finding is in line with previous works (Cecchini et al, 2019;Grayson, 2017;Frydman et al, 2014). Indeed, these authors also found that cutting gains and holding losses are two uncorrelated biases.…”
Section: Resultssupporting
confidence: 92%
“…The results reported by Ahmad (2020) show that disposition effect is positively associated with extraversion and conscientiousness. Cecchini et al (2019) found that disposition effect is positively influenced by extraversion and negatively related to openness and conscientiousness. These authors document that September 2021 edition Vol.17, No.32 www.eujournal.org 305 disposition effect could be determined by two independent psychological biases: holding losses and cutting gains.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…They found three traits related to different outcomes: (a) reward sensitive extroverts quickly sold the stock at a gain to receive a burst of utility; (b) conscientious investors suppressed impulsivity; and (c) conscientious investors patiently waited for (hopefully) higher cumulative returns. Cecchini et al (2019) also highlighted the importance of openness to experience to better value information to achieve higher outcomes. Czerwonka (2019) showed, as many others have before, that Extraversion (positively) and Conscientiousness (negatively) were related to risk-taking; and that men were greater risk takers than women.…”
Section: Personality and Financial Decision Makingmentioning
confidence: 99%
“…Cecchini, Bajo, Russo, and Sobrero () were particularly interested in the “disposition effect”, which is the tendency to cash in quickly financial gains but hold on longer to stocks with losing/falling prices. They found three traits related to different outcomes: (a) reward sensitive extroverts quickly sold the stock at a gain to receive a burst of utility; (b) conscientious investors suppressed impulsivity; and (c) conscientious investors patiently waited for (hopefully) higher cumulative returns.…”
Section: Personality and Financial Decision Makingmentioning
confidence: 99%